A radiological evaluation of loop length change in adjustable versus fixed loop femoral cortical fixation devices in arthroscopic anterior cruciate ligament reconstruction: a prospective study - Sarkar, Aruddha; Sen, Biswarup; Gautam, Manu; Garg, Hitesh; Gupta, Sunanda; Sahni, Saurabh (International Journal of Research in Orthopaedics, 2023)
Background: In anterior cruciate ligament reconstructions, fixed devices require over-drilling to flip the button whereas loops of adjustable devices can be adjusted intraoperatively, and they minimize over-drilling. But they can loosen rendering the reconstruction incompetent. Most studies comparing them are bio-mechanical studies. Our aim was to record and compare loop length change radiologically in adjustable versus fixed devices in clinical settings. Methods: 32 patients were divided into 2 groups of 16 patients each. Hamstring graft were prepared. It was loaded in the suspension device and the apex of the graft was marked using silicon vascular radio-opaque marker. In adjustable devices, lengthening was checked after cycling and re-tensioning was done intra-operatively. Post-surgery, digital X-ray of the knee was taken in true antero-posterior and lateral view. Distance between the centre point of the button and the centre-point of the radio-opaque inert silicon marker was recorded at immediate post-operative and at 6 weeks respectively and compared. Results: 15 patients in each group were incorporated. Intra-operatively, loop lengthening was seen in all 15 patients with adjustable loop and re-tensioning was done. 2 of the 15 cases showed evidence of radiological loop lengthening however in both cases the lengthening was less than 3 mm and thus was not significant. Conclusions: We in in vivo radiology based clinical study did not find any significant loop lengthening in patients with adjustable loop devices. Hence fixed and adjustable loop devices are comparable.